State and Fiqh: Examination of the Legal Status of Divorce in Verstek Decision Number 2939/Pdt.G/2023/PA.Mdn - Maswandi, Maswandi; Frensh, Wenggedes; Siregar, Fitri Yanni Dewi; Hidayani, Sri (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2024)
This research is grounded in Decision Number: 2939/Pdt.G/2023, wherein the presiding magistrate rendered a verdict of Verstek in his consideration of the case. In such cases, the decision is rendered by the court in the absence of either the defendant or their legal representative. The validity of a verstek verdict in the context of the legitimacy of a marriage may be contingent upon the applicable legislation within the jurisdiction in question; thus, this investigation will consider both positive law and Islamic law. The objective of this article is to undertake a critical analysis of the decision rendered in Decision Number: 2939/Pdt.G/2023, which pertains to the use of a verstek decision to terminate a marriage due to childlessness, followed by disputes and quarrels. This research is a normative legal study with a case-based approach. The principal data source is derived from court decisions in the field of marriage law. The analysis reveals that, in Decision Number: 2939/Pdt.G/2023, a verdict of divorce by verstek is considered valid if the stipulated procedures have been followed correctly and the party who is required to be present or provide a defence does not do so without a valid reason. Islamic law also establishes principles of justice and protection of individual rights, including in the marriage process. Accordingly, the legitimacy of a marriage concluded through a verstek verdict may be contingent upon the interpretation of Islamic schools of thought and the legal principles that are embraced. Likewise, in the context of marriage law in Indonesia, a verstek decision in a verstek divorce case can be recognized as valid if it has fulfilled the requirements stipulated in the law. Thus, to determine whether a verstek decision in a marriage is valid or not, it is necessary to consider the applicable legal context, both in terms of civil law and in terms of Islamic law (fiqh) or the applicable marriage law.